Type I Interferons induce endothelial destabilization in Systemic Lupus Erythematosus in a Tie2-dependent manner - Rafael-Vidal, Carlos; Martínez-Ramos, Sara; Malvar-Fernández, Beatriz; Altabás-González, Irene; Mouriño, Coral; Veale, Douglas J.; Floudas, Achilleas; Fearon, Ursula; Reigosa, José María Pego; García, Samuel (Frontiers in Immunology, 2023)
Endothelial cell (EC) dysfunction is a hallmark of Systemic Lupus Erythematosus (SLE) and Tie2 is a receptor essential for vascular stability. Inflammatory processes promote inhibition of Tie2 homeostatic activation, driving vascular dysfunction. In this work we determined whether type I Interferons (IFN) induce Tie2 signalling-mediated endothelial dysfunction in patients with SLE. Serum levels of Angiopoietin (Ang)-1, Ang-2 and soluble (s)Tie1 in patients with SLE and healthy controls were measured by ELISA. Monocytes from patients with SLE and Human Umbilical Vein EC (HUVEC) were stimulated with IFN-α, IFN-β (1000 I.U.) or SLE serum (20%). mRNA and protein expression, phosphorylation and translocation were determined by quantitative PCR, ELISA, Western Blot, flow cytometry and confocal microscopy. Viability and angiogenic capacity were determined by calcein and tube formation assays. We found that sTie1 and Ang-2 serum levels were increased and Ang-1 decreased in patients with SLE and were associated with clinical characteristics. Type I IFN significantly decreased Ang-1 and increased Ang-2 in monocytes from patients with SLE. Type I IFN increased sTie1 and Ang-2 secretion and reduced Tie2 activation in HUVEC. Functionally, type I IFN significantly reduced EC viability and impaired angiogenesis in a Tie2 signalling-dependent manner. Finally, SLE serum increased Ang-2 and sTie1 secretion and significantly decreased tube formation. Importantly, Tie1 and IFNAR1 knockdown reversed these effects in tube formation. Overall, type I IFN play an important role in the stability of EC by inhibiting Tie2 signalling, suggesting that these processes may be implicated in the cardiovascular events observed in patients with SLE.